Study of argon ions density and electron temperature and density in magnetron plasma by optical emission spectroscopy and collisional-radiative model; Resource-Efficient Technologies; Vol. 3, iss. 2 - Evdokimov K. E. Kirill; Konischev M. E. Maxim; Pichugin V. F. Vladimir; Sun Z. (2017, 2017)
Title screen